(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
The levels of proximate composition, minerals, antinutrients, fibre components and calculated parameters for mineral bioavailability were determined in the testa, dehulled and whole seeds of Bambara groundnut on dry weight basis. Proximate levels were (g/100 g): ash (2.46- 4.36); crude fat (2.47-6.99); crude protein (15.2-22.2); crude fibre (1.03-22.9) and carbohydrate (51.6-61.9). The non-starch polysaccharide (NSP) components were (%): ADF, 7.13-29.0 (or 16.1 %-65.5 %); NDF, 1.77-23.6 (or 6.28 %-83.7 %); ADL, 6.15-28.0 (or 14.9 %-67.8 %); cellulose, 1.36-23.3 (or 5.02 %-86.0 %) and hemicellulose, 0.84-26.5 (or 2.86 %-90.1 %). In minerals (mg/100 g): Mn, Co and Cu were not detected; Na, K, Ca, Mg, Fe and P were low in values whereas Zn was high at 11.2-40.2. These parameters were also good for human health: Na/K (0.47-0.51) and Ca/Mg (2.58-4.36). Antinutrient values showed that Phy was high (14.4-29.2 mg/g); oxalate was high (5.02- 8.59 mg/g) and unavailable phosphorus as Pp % of P (10.2-49.3 %). The mineral bioavailability showed Ca/Phy to be good at 0.20-0.89 and [Ca] [Phy]/[Zn] to be good at 0.09-0.23 thereby making Zn bioavailable in all the samples. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17325 Bangladesh J. Sci. Ind. Res. 48(3), 167-178, 2013